Cumulative cultural learning: Development and diversity - Legare, Cristine H. (Proc Natl Acad Sci U S A, 2017)
The complexity and variability of human culture is unmatched by any other species. Humans live in culturally constructed niches filled with artifacts, skills, beliefs, and practices that have been inherited, accumulated, and modified over generations. A causal account of the complexity of human culture must explain its distinguishing characteristics: It is cumulative and highly variable within and across populations. I propose that the psychological adaptations supporting cumulative cultural transmission are universal but are sufficiently flexible to support the acquisition of highly variable behavioral repertoires. This paper describes variation in the transmission practices (teaching) and acquisition strategies (imitation) that support cumulative cultural learning in childhood. Examining flexibility and variation in caregiver socialization and children’s learning extends our understanding of evolution in living systems by providing insight into the psychological foundations of cumulative cultural transmission—the cornerstone of human cultural diversity.